The Sufi Poems of Love: Al Busiri’s Burdah through The Lens of Rumi - Arikhah arikhah (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2022)
Examining the Maḥabbah concept has unavoidably become an interesting study, particularly via tasawuf lenses. Maḥabbah is a spiritual phase that Sufis encounter in many forms and expressions. Many Sufi leaders documented their experiences in literary works, including al-Busiri’s Burdah poems. A work that is regarded to be high literature consists of compliments to the Prophet Muhammad Saw. The purpose of this study is to discuss the Maḥabbah literature of al-Busiri’s Burdah and how the school of love is internalized in his work, where both concerns are examined through Rūmī's literary conceptions that highlight the Maḥabbah as the means of his tasawuf characteristic. This paper is qualitative library research. This study revealed that the Burdah of al-Busiri matches Jalāluddīn Rūmī's expression, which used metaphors, symbolization of love, and the conception of Maḥabbah.Contribution: By investigating Jalāluddīn Rūmī's notion, this study provides understanding and showing the Maḥabbah values found in al-Busiri's Burdah poems while also illuminating features of the historicity of tasawuf around it.